Efficiency of Klanting Crackers Processing Process using A Clean Production Approach UMKM Kamasa Case Study - Melinda Azzahra Putri; Muhammad Indra Darmawan; Ema Lestari (Universitas Darussalam Gontor, 2023)
UMKM Kamasa Kerupuk Klanting needs to implement clean production which aims to reduce waste and increase the efficiency of using raw materials. The objective of the research was to identify the implementation of clean production in Kerupuk Klanting processing and to analyze alternative implementations of clean production economically and technically at UMKM Kamasa Kerupuk Klanting. These stagesof the research were identification of the production process, analysis of net production opportunities, analysis of economic and technical feasibility and election priority cleaner production opportunities with paired comparison questionnaires. Processing of Kerupuk Klanting of cassava-based 80 kg produces an average of 40.25 kg of Kerupuk Klanting and produces 20.4124 kg of solid waste and 525 kg of liquid waste. The recommended net production opportunities are processing cassava peels into compost, processing cassava peels into liquid organic fertilizer and reducing the use of clean water in the cassava washing process by collecting water in the sink and cleaning using a cloth, using sacks directly at the mouth of the grating machine is expected to hold grated cassava spilled on the machine can be recovered, utilization of squeezed wastewater as raw material for cassava starch (tapioca), and use of wood pellets as a substitute for firewood. Priority assessment of clean production opportunities using Expert Choice is Reducing the use of clean water in the cassava washing process by collecting water in the sink and cleaning using a cloth